Enhancement of the Solubility and Dissolution Rate of Rebamipide by Using Solid Dispersion Technique (Part I) - Ismail, Muna Y.; M. Ghareeb, Mowafaq (Iraqi Journal of Pharmaceutical Sciences, 2018)
Solid dispersion is an attractive tool of pharmaceutical technology used to improve the physical properties of drugs. Among these properties is to enhance the solubility of the drugs.Rebamipide is a poorly soluble drug of class IV of biopharmaceutical classification system (BCS).Rebamipide is used as potent antiulcer, mucoprotective drug, by stimulating the generation of prostoglandine enhanced mucosal protection.Rebamipide was formulated as a solid dispersion using different polymers such as pluronic F-127, PEG6000, PVP K30, and TPGS by using different preparation methods solvent evaporation, fusion, and kneading methods.It was seen that rebamipide was successfully dispersed in a homogenous solid dispersion matrix by solvent evaporation method using TPGS (1:15) drug carrier ratio.Moreover, the results revealed that the solubility of rebamipide (23.9µg/ml) increased significantly (p?0.05) by 36.4 x fold to obtain 874µg/ml solubility in rebamipide matrix. On the other hand, characterization of rebamipide solid dispersion using FTIR, DSC, SEM and x-ray diffraction demonstrated no drug polymer interaction, and converting the rebamipide from crystal to amorphous state lattice.